Incidence of Cryptosporidiasis in Human of Al-Hilla City/Iraq - Fatima HA (Journal of Global Pharma Technology, 2018)
During one year period from 2nd January till 31st December 2017 A prospective study was conducted in the children and maternity hospital in Al-Hilla city on the admitted patients. The aim was to identify if cryptosppridial infection exist in this locality, its incidence course of the disease and its treatment. Results showed that Cryptosporidiasis was present, the disease incidence was high and its course is more severe in patients with malnutrition. There was no difference in response of all patients to different lines of treatment.Keywords: Cryptosporidiasis, Malnutrition, Watery diarrhea, Cryptosporidium.